Anonymous

# Can anyone solve this math problem?

factor:

x^2 - 9x + 18

3b^2 - 7b + 4

Relevance

What you need to remember is the simple formula for the problems you're attacking:

(ax - b)(cx - d) = acx^2 - x(bc + da) + bd

1) So let's attack the first problem:

x^2 - 9x + 18

Because there is no integer in front of x^2, we know that a and c are only 1 and your new factor formula looks like:

(x-b)(x-d)

Now the question is, what two numbers can you multiply together to make 18, yet add together to make -9? Start by factoring out 18:

18 = (-1, -18), or (-2,-9), or (-3,-6).

Only 3 and 6 can combine to make -9, and since the values for a and c are the same, it doesn't matter where you place each number. Your answer is therefore:

x^2 - 9x + 18 = (x-3)(x-6)

2) Your next question is a little more difficult, since there is an integer before the b^2 value. But 3 only has one pair of factors: (3,1), so you can plug those into your factor equation:

(3b - ?)(b - ?)

Now the second part is a bit trickier. You need two numbers that when multiplied equal 4, but you have to place them in the right place so that one of them will multiply with 3 before being added to equal -7. So let's factor out 4's pairs:

4 = (-1, -4), or (-2, -2)

At this point, you can try plugging in each pair. If you plug in the second pair, you end up with -8b as a middle term. So you know it has to be the first pair (-1,-4). If you place the -1 with the 3b, you'll end up with -13b. But if you place the -4 with the 3b, you'll end up with -7b, and your answer!

3b^2 - 7b + 4 = (3b-4)(b-1)

Hope this helps, and remember that if your middle terms were +9x and +7b, your factors would be positive!

• Anonymous

It factors to (x-3)(x-6)=0 x=3,6

(3b-4)(b-1)=0 b=1, b=4/3

• 2x + 2y = 20 utilising the simultaneous approach 2x - 2y = 4 ____________ 4x = 24 ( divide through 4) x = 6 replace x in between both equations 2x + 2y = 20 2 (6) + 2y = 20 12 +2y = 20 2y = 20 - 12 2y = 8 (divide through 2) y = 4 answer : X = 6 , Y = 4

• its a factor problem not a solve and its

(x-3)(x-6)

(3b-4)(b-1)

• (x-6) (x-3)

(3b-4) (b-1)

If you want help knowing how i got this just send a message and i'll try to explain it to you better.

• x=3

x=6

b=1

b=1.3333

• Anonymous

As Mr. P. Nuss would say, "Let me take a whack at it!"

• you didn't give an equals sign so there is no actual problem

• (x-6)(x-3)

???

• Anonymous